2017
DOI: 10.1515/pcard-2017-0002
|View full text |Cite
|
Sign up to set email alerts
|

Selected data from the Polish National Prenatal Cardiac Pathology Registry from the year 2016

Abstract: Introduction: Analysis have been subjected to evaluate standard data reports from the Polish National Prenatal Cardiac Pathology Registry from the year 2016, compared to previous years. Material and methods: The methodology of this work was comparison of the data from previous years that have been published in the Prenatal Cardiology and records generated in www. orpkp.pl from the year 2016. The total number of records entered in the Registry in the year 2016 was n=774. Results: Top 10 most common prenatal CHD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
(9 reference statements)
1
4
0
Order By: Relevance
“…Nowadays, the effects of Poland's prenatal CHD screening are similar to results obtained across the rest of Europe, where the rate of detection of univentricular defects is greater than 85% . According to the Polish National Registry of Cardiac Surgery, in 2015 and 2016, 87.7% and 98.9% of newborns with HLHS were diagnosed prenatally, respectively . Over the period of our study, we observed that the mean gestational age of HLHS detection decreased by 5 weeks, from 26.0 weeks in 2004 to 20.8 weeks in 2016, and this was a statistically significant improvement.…”
Section: Discussionsupporting
confidence: 81%
“…Nowadays, the effects of Poland's prenatal CHD screening are similar to results obtained across the rest of Europe, where the rate of detection of univentricular defects is greater than 85% . According to the Polish National Registry of Cardiac Surgery, in 2015 and 2016, 87.7% and 98.9% of newborns with HLHS were diagnosed prenatally, respectively . Over the period of our study, we observed that the mean gestational age of HLHS detection decreased by 5 weeks, from 26.0 weeks in 2004 to 20.8 weeks in 2016, and this was a statistically significant improvement.…”
Section: Discussionsupporting
confidence: 81%
“…These centers sent a protocol from examinations to the main center. The Polish centers of prenatal cardiology have rank C or B in the prenatal cardiology system in Poland (www.orpkp.pl) (accessed on 20 October 2022), which means that they are referral centers (mostly patients with high-risk pregnancies; more than 100 congenital heart defect cases per year) and perform referral fetal echocardiography and"genetic" ultrasonography examinations [13]. The data of the patients were de-identified and this was an observational study and we did not change the method of medical management but focused on the interpretation of additional collected data, thus; a new approval from the Ethical Committee was not necessary.…”
Section: Methodsmentioning
confidence: 99%
“…Hypoplastic left heart syndrome (HLHS) is one of the most common, prenatally diagnosed congenital heart diseases (CHD) [1][2][3]. In this CHD, the right ventricle serves as the main pump supplying blood to both pulmonary and systemic circulation, while the left ventricle has almost no haemodynamic function.…”
Section: Introductionmentioning
confidence: 99%